Later Diagnosis of Cystic Fibrosis with Negative Newborn Screen: Importance of the Clinical Picture - B, Batoczki; AE, Galvis; IS, Pecson; J, Meyers; C, Nakamura (Archives of Clinical and Medical Case Reports, 2019)
Cystic fibrosis (CF) is the most common inherited life-limiting disorder among Caucasians. The implementation of CF newborn screening has enabled early diagnosis and prompt treatment onset. However, several factors may affect circulating levels of immunoreactive trypsinogen leading to a normal CF newborn screen. This case aims to highlight the importance of taking clinical manifestations as a strong factor for the diagnosis of CF even in the presence of a negative newborn screen. This may allow early referral to a specialized CF center where the onset of appropriate treatment can be implemented, thereby positively impacting the course of the disease.